PERLAKUAN BIOPRIMING KOMBINASI AIR KELAPA MUDA DAN TRICHODERMA TERHADAP VIABILITAS DAN VIGOR BENIH CABAI KADALUARSA (Capsicum annuum L.) - Hasanuddin Hasanuddin; Vina Maulidia; Syamsuddin Syamsuddin (Universitas Teuku Umar, 2018)
The objective of this research was to study the effect of young coconut water concentration, Trichoderma species, and the interaction which is used in the biopriming process to increased viability and vigor of expired chili seed. This research was conducted at Seed Science and Technology Laboratory and Plant Disease Laboratory, Faculty of Agriculture, Syiah Kuala University. The design used completely randomized design (CRD) 4 x 4 factorial with three replications. Factors studied consisted of young coconut water concentration factor (0%, 10%, 15% and 20%) and Trichoderma species (without Trichoderma, Trichoderma virens, Trichoderma harzianum and Trichoderma asperellum). Seed viability and vigor were estimated by maximum growth potential, percentage of germination, relative growth speed, simultaneity grow, required time to reach 50% total of relative germination (T), Index of vigor, normal seedling wet weight and normal seedling dry weight. The expired chili seed treatment with concentration young coconut water 15% showed the best value to the increasing of viability and vigor of chilli seed. Species of Trichoderma harzianum showed the best value to the increasing of viability and vigor of chilli seed. There is a significant interaction between the young coconut water and Trichoderma species, the best combination was found in concentration of 15% young coconut water and Trichoderma harzianum to increase the viability and vigor of chilli seed. Keywords: index of vigor, normal seedling dry weight, percentage of germination growth speed